REDUCING VERTICAL AND ANGULAR ACCELERATIONS WITH NONLINEAR ASYMMETRICAL SHOCK ABSORBER IN PASSENGER VEHICLES - Silveira, Marcos [UNESP]; Pontes, Bento R. [UNESP]; Balthazar, Jose M. [UNESP]; ASME (Amer Soc Mechanical Engineers, 2014)
The behaviour of linear and nonlinear shock absorbers are compared to diminish vertical and angular (pitch) accelerations of passenger vehicles, improving comfort by result. A 4-dof half-car model is used with three configurations of dampers: symmetrical, asymmetrical and front asymmetrical. The analyses use three standard road inputs and include variation of the severity parameter, the asymmetry ratio and the velocity of the vehicle. The comparison shows that the asymmetrical system, with nonlinear characteristics, tends to have a smoother and more progressive behaviour. The results show that the use of the front asymmetrical system diminishes angular oscillations of the vehicle. As lower levels of acceleration are essential for improved ride comfort, the use of asymmetrical systems for vibrations and impact absorption is a superior choice for passenger vehicles.